Splash 12 celebrating artistic vision - Rubin Wolf, Rachel (The best of water color, 2011)
"The Splash" series showcases the finest watercolour paintings being created today. Readers gain insight into methods of the best contemporary watercolour artists in the 12th edition of this top-selling series. This title features about 126 paintings by 100 artists selected from over 1500 submissions from watercolour and water-media painters across the world. Each painting is accompanied by a caption that offers instructive information on the theme of 'celebrating artistic vision' as interpreted by the contributing artists, revealing loads of instructional and inspirational tips on the watercolour medium.